2022
DOI: 10.1161/strokeaha.122.039575
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Cerebral Venous Thrombosis due to Vaccine-Induced Immune Thrombotic Thrombocytopenia After the Acute Phase

Abstract: Background: Cerebral venous thrombosis (CVT) due to vaccine-induced immune thrombotic thrombocytopenia (VITT) is a severe condition, with high in-hospital mortality rates. Here, we report clinical outcomes of patients with CVT-VITT after SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2) vaccination who survived initial hospitalization. Methods: We used data from an international registry of patients who developed CVT within 28 days of SARS-Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 11 publications
(19 reference statements)
0
9
0
Order By: Relevance
“…Almost 90% achieved functional independence, as was reported for CVST-VITT irrespective of EVT. 20 Nevertheless, half of the CVST-VITT patients treated with EVT died during the initial admission, which is similar to the mortality in patients without EVT, but significantly higher than in the EVT studies of CVST unrelated to vaccination (12%). 4,6 This is most likely due to the greater severity of CVST-VITT in general.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Almost 90% achieved functional independence, as was reported for CVST-VITT irrespective of EVT. 20 Nevertheless, half of the CVST-VITT patients treated with EVT died during the initial admission, which is similar to the mortality in patients without EVT, but significantly higher than in the EVT studies of CVST unrelated to vaccination (12%). 4,6 This is most likely due to the greater severity of CVST-VITT in general.…”
Section: Discussionmentioning
confidence: 69%
“…2 Compared to previous anecdotal reports, the rates of technical success, complications and favorable outcomes were similar, while mortality was higher in our cohort (50% vs 27%, Supplemental Table ). However, the mortality rate of 27% is lower than in CVST-VITT in general (40%) 20 and might be subject to reporting bias, as it is based on single cases and small cohorts up to n = 6. If not available carried forward from admission (n = 3 for hemorrhagic lesion, D-Dimer and fibrinogen, n = 5 for platelet count).…”
Section: Discussionmentioning
confidence: 89%
“…This proportion is in line with our previous report on outcomes of CVST-VITT patients in the acute phase of their presentation. At the 5-month follow-up, almost 90% had regained functional independence [10,22,23]. Nevertheless, due to the limited size of this substudy cohort, these numbers should be interpreted with caution.…”
Section: Surgical Cvst-vitt (Nmentioning
confidence: 83%
“…There are varying reports of whether females are more at risk for CVST in the context of VITT. In an observational study ( n = 60) of CVST occurring within 28 SARS-CoV-2 vaccination, 75% were female [ 42 ]. A female predominance (81%) was also reported in an international registry of CVST within 28 days of SARS-CoV-2 vaccination [ 43 ].…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Another study of VITT-associated CVST ( n = 78) reported an in-hospital mortality rate of 47%, compared with 3.9% for CVST in historical, non-VITT controls [ 43 ]. The highest risk of death is during the acute phase of CVST, with a lower frequency of adverse outcomes beyond the acute phase [ 42 ]. CVST is often associated with other thromboembolic events in up to 36% of VITT patients compared to 4.9% in non-VITT controls [ 43 ].…”
Section: Clinical Presentationmentioning
confidence: 99%